The Inconsistency of the Applicability Norms in the Law on the Special Region of Jakarta Province: The Impact on the Legitimacy of the Capital City of Indonesia during the Relocation Transition Period - Diastama Anggita Ramadhan; Enny Nurbaningsih; Mailinda Eka Yuniza (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The relocation of the capital city of the Republic of Indonesia from DKI Jakarta Province to the Indonesian archipelago has raised several issues, one of which is for the former capital city. The problem that arises lies in the regulations that serve as the legal basis for the Special Region of Jakarta Province after it is no longer the capital city. Inconsistencies in norms occur between Law Number 2/2024 (UU 2/2024) and Law Number 151/2024 (UU 151/2024), which is an amendment to Law 2/2024. Law 2/2024 states that the enactment of the law is still awaiting the issuance of a Presidential Decree regarding the official relocation of the capital city. On the other hand, Law 151/2024 is declared to be in effect on the date of its promulgation. Law 151/2024 was formed with the aim of recognizing the winner of the 2024 general election from the electoral district of DKI Jakarta Province as the winner of the general election from the Special Region of Jakarta Province. The type of research used in this study is qualitative research using secondary data. This type of qualitative research was chosen to understand the issues that arise related to the inconsistency of norms between Law Number 2/2024 concerning the Special Region of Jakarta Province and its amendments through Law Number 151/2024. This study uses a descriptive research approach. The descriptive approach aims to accurately explain the legal materials obtained. In addition to descriptive, this study also uses a prescriptive approach. There are two (2) findings of this study: first, this inconsistency of norms impacts the validity of all legal products which are made by Provincial officials which is should be made by, for, and on behalf of the Special Region of Jakarta Province. Second, there are constitutional issues arising from legal uncertainty regarding the position of the nation's capital during the transition period.